Defining and measuring the productive office. Issue 1 (14th March 2019) - Harris, Rob
Abstract : Purpose: This paper aims to provide a perspective on the office productivity debate, with a particular focus on providing a framework for examining those factors relating to the design and management of the office environment. Design/methodology/approach: The approach taken has been to examine the plethora of factors that might be involved, principally through a literature review, and then to group these into four generic areas of enquiry. Within each of these, potential measures of productivity are described, and these are connected to building lifecycle decisions. Findings: Combined, the findings produce a practical framework within which various actors in the design, delivery and management offices can understand and influence the productivity question. In this way, the findings have practical implications rather than simply describing the factors that influence productivity. Originality/value: The paper develops a report produced in 2017 for the British Council for Offices. Building on the main findings of the original work, this paper expands the literature review, provides more context regarding the significance of office productivity and expands upon the conclusions. The author fully acknowledges the contributions of the whole research team behind the original paper. The originality of the work lies in its development of a framework that can be applied by practitioners in the built environment.